Pigmented Oral Lichen Planus: A Case Report - Firstine Kelsi Hartanto; Thomas George Kallarakal (Faculty of Dentistry, Universitas Trisakti, 2017)
Background: Lichen planus is a chronic muccocutaneous inflammatory disorder. Oral lichen planus (OLP) has certain specific characteristics in its clinical presentation, but can also be presented in forms resembling other diseases. This may introduce difficulty in the diagnostic process. It has been reported that OLP affects between 0.1 to 4% individuals, predominantly women and people over 40 years old. Case Report: A 46-year-old woman complained of a non-healing ulcer present for 1.5 months. Intraorally, multiple white striae with prominent central areas of brownish hyperpigmentation were apparent on the right and left buccal mucosa, right and left buccal sulcus, and lateral and dorsum of the tongue. A biopsy was completed and the histopathology features confirmed the diagnosis of OLP. For the initial treatment, a topical corticosteroid was prescribed, followed by steroid mouthwash. Response to this treatment was positive. OLP has been frequently reported to affect women over the age of 40, with psychological stress as a primary predisposing factor. The clinical presentation is characteristic of Wickham’s striae with erosive areas. However, a biopsy and histopathological examination is mandatory to confirm the diagnosis. The clinical feature of pigmented OLP has been reported and confirmed by microscopic finding of band-like lymphocytic appearance which is the pathognomonic features of OLP, along with basal cell liquefaction degeneration, and melanin in continence at the lamina propria. Conclusion: Pigmented OLP is a variant of erosive OLP. Anamnesis, clinical presentation, and histopathological examination confirm diagnosis.